Correction to: Fluid handling and blood flow patterns in neonatal respiratory distress syndrome versus transient tachypnea: a pilot study - Rana Ismail; Prashanth Murthy; Ayman Abou Mehrem; Zhiying Liang; Amelie Stritzke (BMC, 2022)
An amendment to this paper has been published and can be accessed via the original article.